The life & death of the Solid South : a political history - Grantham, Dewey W. (New perspectives on the South., 1988)
Southern-style politics was one of those peculiar institutions that differentiated the South from other American regions. This system -- long referred to as the Solid South -- embodied a distinctive regional culture and was perpetuated through an undemocratic distribution of power and a structure based on disfranchisement, malapportioned legislatures, and one-party politics. It was the mechanism that determined who would govern in the states and localities, and in national politics it was the means through which the South's politicians defended their region's special interests and political au.